Digital Multimodal Composing (DMC) Using Canva: EFL Students' Perspectives - Alfathira, Syifa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Kurikulum Merdeka is one of the government's policies to improve the quality of learning by integrating media and technology into learning activities. Making use of technology in Kurikulum Merdeka and multimodal approach can be an appropriate alternative to help students improve the quality of their learning. For example, Digital Multimodal Composing (DMC) task using Canva resulted from combining technology implementation and multimodality. This study aims to analyze EFL students’ perspectives on using Canva to complete Digital Multimodal Composing (DMC) tasks which applied a descriptive qualitative method with questionnaire and interview as instruments. The respondents are fourth semester students of the English Language Education Study Program, Faculty of Teachers Training and Educational Sciences, Pakuan University. The results showed students’ positive perspectives regarding Canva as a very useful for completing DMC tasks and is the right solution because of the ease of use, exciting and useful features and also can develop students' 4Cs abilities and understanding of concepts of multiliteracy, multimodal, and infographics. The combination of Canva and DMC enhances students' learning motivation, produces high-quality infographics, and demonstrating their effective utilization of technology. Additionally, it is recommended that further research analyze this topic with a large scope of respondents and with additional instruments so that the research data obtained can be more varied, as well as exploring other digital tools for completing multimodal tasks. It is hoped that this study can serve as a valuable reference for future studies on the same topic.